2014
DOI: 10.1088/0953-4075/48/2/025501
|View full text |Cite
|
Sign up to set email alerts
|

Selective dynamical decoupling for quantum state transfer

Abstract: Abstract. State transfer across discrete quantum networks is one of the elementary tasks of quantum information processing. Its aim is the faithful placement of information into a specific position in the network. However, all physical systems suffer from imperfections, which can severely limit the transfer fidelity. We present selective dynamical decoupling schemes which are capable of stabilizing imperfect quantum state transfer protocols on the model of a bent linear qubit chain. The efficiency of the schem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Practically speaking, however, such perfect state transfer is difficult due to the unwanted influences of the environment. To remove this detrimental effect, pulse sequences [60] have been considered and the direct modulation of the spinspin coupling has also been investigated [61]. With our scheme, as we have discussed, local noise terms can be eliminated to lowest order by applying a static as well as oscillating control fields.…”
Section: Quantum State Transfermentioning
confidence: 99%
“…Practically speaking, however, such perfect state transfer is difficult due to the unwanted influences of the environment. To remove this detrimental effect, pulse sequences [60] have been considered and the direct modulation of the spinspin coupling has also been investigated [61]. With our scheme, as we have discussed, local noise terms can be eliminated to lowest order by applying a static as well as oscillating control fields.…”
Section: Quantum State Transfermentioning
confidence: 99%
“…If we have control over all sites we can globally design the dynamics such that the walker is transferred between a selected pair of vertices at a certain time. For the continuous time evolution, where the dynamics is governed by the Schroedinger equation with a given hamiltonian, the problem was investigated to large detail in the context of spin chains [5][6][7][8][9][10], discrete quantum networks of various topologies [11][12][13][14][15] and continuous time quantum walks [16][17][18][19][20]. In the discrete time case this approach was studied on various graphs such as circle [21,22], regular graphs [23] or more general networks [24].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years dynamical decoupling has been scrutinized more closely both from the theoretical [10][11][12][13] and the experimental side [15][16][17][18][19]. It has been shown that this method can also tailor the Hamiltonian evolution into a desired one [20,21]. Therefore, it can be called dynamical control and not only dynamical decoupling.…”
Section: Introductionmentioning
confidence: 99%